The Effect of Leaflet as Educational Media on the Pre-Conception Nutrition for Prospective Bride and Groom - Arfah Husna; Marniati Marniati; Enda Silvia Putri; Siti Maisyaroh Fitri Siregar; Siti Arafah Carolina (International Conference on Multidisciplinary Research, 2022)
Nutritional status of the prospective bride or pre-wedding woman for three or six months during the preconception period will determine the condition of the baby being born. Pre-conception perfect nutrition is the key to the birth of a normal and healthy baby as one of the specific nutrition intervention efforts is the prevention of stunting cases.. This study aims to examine the effect of the intervention of leaflet media education methods on increasing knowledge about preconceptional nutrition of the bride and groom. Methods: This study uses a Quasi-Experimental design with one group before and after intervention design on 20 prospective brides at KUA, Johan Pahlawan District, West Aceh Regency. Result: Based on the results of the bivariate test, it is known that there is a significant effect of the leaflet media education method on increasing knowledge about preconception nutrition of the bride and groom. To conclude, the intervention of the leaflet media education method has an effect on increasing knowledge, about preconception nutrition of the bride and groom.   Keywords: Prospective Bride and Groom, Preconception Nutrition, Knowledge, Leaflet